MOTIVATION OF BADMINTON ATHLETES EARLY AGE GROUP PRACTICE BADMINTON IN THE PBSI MERAUKE REGENCY - Pranata, Didi Yudha; Khoirul Hidayat, Afif; Purnomo, Edi (Teunuleh Publisher, 2022)
badminton is an integral part of overall sports activities which have the goal of improving physical fitness and achievement. At the early age group stage, the badminton training process is also designed to stimulate organic, motor, intellectual and emotional growth. In physical conditions that are still in the initial growth stages, athletes in the early age group naturally experience many obstacles when undergoing the training process, so coaches, parents and administrators of badminton sports must pay special attention to the level of physical condition and motivation of each athlete. This research was conducted with the aim of knowing the level of motivation possessed by badminton athletes in the early age group PBSI Merauke Regency practicing badminton. This study uses a quantitative research approach where data collection uses a survey method with a total of 30 questions. Based on the results of instrument validation by expert judgment, the result was that there were 3 question items that turned out to be inappropriate or invalid, so that the remaining 27 question items were valid and feasible to be used as data collection instruments. The subjects used in this study were 34 athletes consisting of 8 female athletes and 26 male athletes. Based on the results of the study it can be seen that the motivation of badminton athletes in the early age group PBSI Merauke Regency to practice badminton is in the very high category, this statement is proven by obtaining research data which shows that there are 24 athletes or 70.59% who have very high motivation in playing badminton, there were 10 athletes or 29.41% who had high motivation in playing badminton, and there was not a single athlete or 0% who had motivation in the low and very low categories of playing badminton.